The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1086/427811
|View full text |Cite
|
Sign up to set email alerts
|

Function of HAb18G/CD147 in Invasion of Host Cells by Severe Acute Respiratory Syndrome Coronavirus

Abstract: To identify the function of HAb18G/CD147 in invasion of host cells by severe acute respiratory syndrome (SARS) coronavirus (CoV), we analyzed the protein-protein interaction among HAb18G/CD147, cyclophilin A (CyPA), and SARS-CoV structural proteins by coimmunoprecipitation and surface plasmon resonance analysis. Although none of the SARS-CoV proteins was found to be directly bound to HAb18G/CD147, the nucleocapsid (N) protein of SARS-CoV was bound to CyPA, which interacted with HAb18G/CD147. Further research s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
257
0
6

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 266 publications
(280 citation statements)
references
References 18 publications
6
257
0
6
Order By: Relevance
“…It has been demonstrated that elevated HAb18G/CD147 expression is correlated with the progression and invasion potential of human hepatoma cells [13,[22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that elevated HAb18G/CD147 expression is correlated with the progression and invasion potential of human hepatoma cells [13,[22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…A study using unbiased yeasttwo-hybrid screening discovered that CypA bind to Nsp1 protein of SARS-CoV (Pfefferle et al, 2011) and HCoV-NL63 virus. The nucleocapsid (N) protein of SARS-CoV interacts with CypA, which mediates HAb18G/ CD147 to interact with SARS-CoV N protein, and thus helps in viral replication in 293 cells (Chen et al, 2005). Furthermore, silencing of the cellular CypA through siRNA inhibits the replication of HCoV-NL63 virus in Caco-2 cells, revealing the requirement of CypA for CoV infection (Carbajo-Lozoyaa et al, 2014).…”
Section: Coronavirusesmentioning
confidence: 99%
“…The chemotaxis activity of CyPA is dependent upon its interaction with CD147, and inhibition of the CyPA/CD147 interaction with anti-CD147 mAb or CsA greatly decreases migration of immune cells to the sites of inflammation in mouse models of diseases such as acute lung injury, asthma, and rheumatoid arthritis (1, 16 -18). Moreover, CyPA/CD147 interaction also plays a role during the infection of many viruses, including HIV-1 (19), severe acute respiratory syndrome coronavirus (SARS-CoV) (20), vaccinia virus, vesicular stomatitis virus, and others (21,22). In addition, the cell surface expression of CD147 was reported to be regulated by the cytosolic CyPA (23).…”
mentioning
confidence: 99%